A comprehensive investigation of the behaviour of phenolic compounds in legumes during domestic cooking and in vitro digestion. (1st July 2019) - Giusti, Federica; Capuano, Edoardo; Sagratini, Gianni; Pellegrini, Nicoletta
Highlights: Phenolics occurrence in cooked legumes and in their soaking and boiling water. Free and bound phenolic compounds distribution in seed coats and cotyledons. Free and bound phenolics bioaccessibility assessed in vitro . Only a fraction of legume phenolics is bio-accessible after cooking and digestion. Abstract: Legumes represent staple foods rich in phenolic compounds, which are often consumed after soaking and boiling. This study determines the fate of phenolic compounds from six legumes varieties belonging to the species Lens culinaris Medik., Phaseolus vulgaris L. and Cicer arietinum L . after soaking, boiling and digestion. To this purpose, a new HPLC-DAD method was developed and validated. Results show that the cooking process strongly reduces the content in free and bound phenolic compounds and that the processing water is a valuable source of phenolics. Bioaccessibility of phenolics from the legume matrix was investigated separately in the coat and the cotyledons of three chosen varieties (black beans, black lentils and pinto beans) by means of a standardized in vitro digestion protocol. Results showed that only a fraction of the phenolic compounds is bioaccessible, which may have implications for human health.